(untitled) (Nóema, 2012)
Our aim is to investigate the origin of self-consciousness by means of a philosophical inquiry that takes Darwin’s investigations as its starting point. We then relate this to conceptions of self-consciousness in the pragmatism of Mead and Wright in order to bring some central concepts (such as meaning, voice and intersubjectivity) into focus. We than develop them through a systematic and genealogical reconstruction with the help of some classical phenomenological positions and the philosophy of Carlo Sini.